Hemostatic effect of intrauterine balloon for postpartum hemorrhage with special reference to concomitant use of "holding the cervix" procedure (Matsubara). (March 2017) - Ogoyama, Manabu; Takahashi, Hironori; Usui, Rie; Baba, Yosuke; Suzuki, Hirotada; Ohkuchi, Akihide; Matsubara, Shigeki
Abstract: Objective: The intrauterine balloon (Balloon) has recently been widely used to achieve hemostasis for postpartum hemorrhage (PPH). We concomitantly used a novel method, "holding the cervix", with the Balloon to prevent Balloon prolapse and achieve hemostasis. We aimed to clarify the following three factors: 1) hemostatic success rate of Balloon use for PPH, 2) effect of holding the cervix on Balloon prolapse, and, 3) the rate of bleeding after Balloon insertion, possibly predictive of Balloon failure. Study design: We retrospectively examined 80 patients undergoing Balloon application for PPH in our institution. We defined "success" as achieving hemostasis with no requirement of additional invasive procedures, and "failure" as their requirement. Between success vs. failure, several parameters were compared. For statistical analyses, Fisher's exact test and Wilcoxon rank sum test were applied. Results: Excluding "unable to insert" patients, "holding the cervix" was performed in 56 (75%). Prolapse was less likely to occur in patients with than in those without "holding the cervix" (4 vs. 11%, respectively). The success rate in patients with "Balloon + holding the cervix" was 94%. Treatment for atonic bleeding and placenta previa (PP) showed similarly high success rates (97 and 94%, respectively). The rate of bleeding following Balloon insertion was significantly higher in failure than success cases (P = 0.03) and all failure cases showed bleeding >250 mL/h. Conclusions: The "Balloon + holding the cervix" strategy achieved hemostasis in over 90% of primary PPH. Treatment: for not only atonic bleeding but also PP showed a high success rate. Bleeding >250 mL/h after Balloon insertion may indicate the requirement of additional invasive procedures.